Robust hybrid-entanglement for misalignment-resilient free-space QKD - Omshankar; Vivek Venkataraman; Joyee Ghosh (APL Quantum)
Polarization-entangled photon-based quantum key distribution (QKD) has seen notable advancements, requiring users to share a common frame of reference that might lead to a significant technical overhead of constant monitoring of their frame of reference. In this work, we characterize and demonstrate hybrid entangled photon pairs for their utilization in rotational alignment-free QKD applications. By employing vortex half-wave retarders that have an azimuthally varying fast axis with a topological charge of q=12, we generate high brightness rotationally invariant hybrid entangled photons and show their resilience against the misalignment of the frame of reference. We demonstrate high fidelity (>92%) entanglement and depict a low quantum bit error rate (QBER) of ∼5−6% (lower than the threshold value of 11%) at a significantly high angle of misalignment θ>45°), in contrast to the polarization-entangled photon pairs that suffer from the degradation of entanglement quality due to a rotational misalignment between the reference frame of communicating entities. The rotationally invariant hybrid photon pairs with robust entanglement properties offer a significant advantage for secure and reliable quantum communication, making them lucrative candidates for applications such as satellite-to-satellite and ground-to-satellite QKD networks. We also show the reliability and stability of the entangled photon source over a long period (measured over 6 h) by demonstrating the BBM92 protocol with a raw key rate of ∼2.8 kbps and a QBER of ∼5% in a single-pass configuration. The performance metrics of our quantum source, measured with conventional avalanche photodiodes (SPADs, quantum efficiency ∼60%, dark counts ∼40 cps), are among the best values reported so far with these detectors.